2002
DOI: 10.4269/ajtmh.2002.67.423
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathologic toxicity of artemisinin derivatives in a mouse model.

Abstract: Abstract. Intramuscular administration of high doses of artemether and arteether to experimental mammals produces selective damage to brain stem centers involved predominantly in auditory processing and vestibular reflexes. The relationship between clinical signs of neurotoxicity and neuropathologic toxicity was studied in the mouse. Intramuscular artemether (50−100 mg/kg/day for 28 days) caused dose-dependent neuropathologic damage to the brain stem. There was no pathologic evidence of neuronal death in mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(44 citation statements)
references
References 30 publications
(43 reference statements)
2
37
0
1
Order By: Relevance
“…Another possible exp lanation is that the drug may affect balance, and as such,upright posture. Earlier studies have shown that some nuclei of the Brainstem, especially those involved in auditory processing and vestibular reflexes, were selectively damaged by high and prolonged Artemisinin administration [8], resulting in abnormal gait and loss of balance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possible exp lanation is that the drug may affect balance, and as such,upright posture. Earlier studies have shown that some nuclei of the Brainstem, especially those involved in auditory processing and vestibular reflexes, were selectively damaged by high and prolonged Artemisinin administration [8], resulting in abnormal gait and loss of balance.…”
Section: Discussionmentioning
confidence: 99%
“…the trapezoid nucleus, the gigantocellu lar reticu lar nucleus and the inferior Cerebellar peduncle [6]. In the rat, the target brainstem nucleus consistently and most severely affected is the nucleus of the trapezo id body [7] [8]. Changes in the affected neurons were loss of Nissl substance, perikaryonal swelling, margination of the nucleus (nucleus accentricity), nucleolar changes, and increased perikaryonal eosinophilia with occasional clu mp ing of eosinophilic debris [6].…”
Section: Background Informationmentioning
confidence: 99%
“…Neurological findings included gait disturbance, loss of spinal and pain response reflexes, and prominent loss of brain stem and eye reflexes. It has been reported that artemether TM produces dose-dependent neuropathological damage to the brain-stem in the mouse (Nontprasert et al, 2002). The neurons in the lower brain-stem trapezoid nucleus, the gigantocellular reticular nucleus, and the inferior cerebella peduncle were the most sensitive to the toxic effects of artemether TM (Nontprasert et al, 2002).…”
Section: Introductionmentioning
confidence: 96%
“…It has been reported that artemether TM produces dose-dependent neuropathological damage to the brain-stem in the mouse (Nontprasert et al, 2002). The neurons in the lower brain-stem trapezoid nucleus, the gigantocellular reticular nucleus, and the inferior cerebella peduncle were the most sensitive to the toxic effects of artemether TM (Nontprasert et al, 2002). Most importantly, it has been shown that in vitro artemisinin induces oxidative stress in cultured neurons, as indicated by an increase in reactive oxygen species and extensive lipid peroxidation (Schmuck et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…It is used in combination therapy and is effective in cases of uncomplicated P. falciparum. Several studies on artesunate showed evidence of toxicity on the brain stem [17,18], superior colliculus [19], stomach [20], testis [21] and liver [22]. The present study evaluated the toxicological influence of different artesunate dosage administration in Albino rats, as administered to human.…”
Section: Introductionmentioning
confidence: 99%